Cell growth and division processes are differentially sensitive to cadmium in Scenedesmus quadricauda - Bisová, K; Hendrychová, J; Cepák, V; Zachleder, V (Folia microbiologica, 2003)
The effect of cadmium on growth processes (accumulation of RNA, proteins and cell volume), cell cycle reproductive events (DNA replication, mitosis, protoplast fission and daughter-cell formation) and the regulatory activity of histone H1 kinases were monitored in synchronized cultures of the chlorococcal alga Scenedesmus quadricauda. Distinct dosage-dependent inhibitory effects of cadmium ions were found in individual growth and reproductive processes. At concentration of about 60 mumol/L CdCl2, the growth processes were slowed down after about half of the cell cycle but the cells grew to the same or larger size than did untreated cells. At higher concentration, the growth became progressively inhibited, being completely blocked above 240 mumol/L. Total RNA accumulation was the most sensitive growth process. Each of the reproductive events was a target for cadmium ions with increasing sensitivity in the following order: DNA replication, mitosis, protoplast fission and daughter cell formation. Throughout the entire experiment, the activity of "mitosis-specific" histone H1 kinases was negligible in the cadmium (60 mumol/L CdCl2) treated cultures, whilst that of the control culture varied, peaking just prior to nuclear divisions. The activity of "growth-associated" histone H1 kinases was not affected by cadmium ions. No effect was found if cadmium was present during the precommitment period. The longer the period in the presence of cadmium, the stronger inhibition of reproductive events.
Keywords: kultivační média; proteinkinasy; Scenedesmus; Cadmium Chloride; Protein Kinases; Cell Division; buněčné jádro; Cell Nucleus; chlorid kademnatý; Culture Media; buněčné dělení